1994
DOI: 10.1113/expphysiol.1994.sp003792
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high concentrations of inspired oxygen on middle cerebral artery blood velocity measured by transcranial Doppler

Abstract: SUMMARYThe effects of high concentrations of inspired oxygen on cerebrovascular haemodynamics were studied in healthy human volunteers using transcranial Doppler measurements of middle cerebral artery blood velocity. If the end-tidal carbon dioxide level was kept constant, the measured blood velocity and the calculated Pulsatility Index showed no significant change when subjects were breathing 21, 40, 75 or 100% oxygen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 10 publications
0
8
1
Order By: Relevance
“…The fall in VIWM with hyperoxia in our study was 4 % (control protocol). This was in contrast to the results of both Ellingsen et al (1987), who found no fall in CBF when PET,02 was raised from 100 to 250 mmHg, and Bew et al (1994), who found no changes in CBF in response to inspired 02 concentrations of 21, 40, 75 and 100 %. However, the value was substantially below that of Purves (1972), who reported a fall in CBF of 11-14% upon inhalation of 85-100 % oxygen.…”
Section: Techniquescontrasting
confidence: 99%
“…The fall in VIWM with hyperoxia in our study was 4 % (control protocol). This was in contrast to the results of both Ellingsen et al (1987), who found no fall in CBF when PET,02 was raised from 100 to 250 mmHg, and Bew et al (1994), who found no changes in CBF in response to inspired 02 concentrations of 21, 40, 75 and 100 %. However, the value was substantially below that of Purves (1972), who reported a fall in CBF of 11-14% upon inhalation of 85-100 % oxygen.…”
Section: Techniquescontrasting
confidence: 99%
“…The raw power and P episode values were averaged across all participants and across all electrodes to demonstrate the gross differences between the four conditions. Examining eyesclosed and eyes-opened trials separately, we performed a cluster-based statistical analysis of the effect of hyperoxia across frequencies and electrodes (Bew, Field, Droste, & Razis, 1994;Desai, Tailor, & Bhatt, 2015;Kety & Schmidt, 1948;Pack, Cola, Goldszmidt, Ogilvie, & Gottschalk, 1992;Tsanov, Chah, Reilly, & O'Mara, 2014). The effect of hyperoxia was assessed at every electrode and every sampled frequency by a two-tailed uncorrected paired t-test with an alpha set to 0.05.…”
Section: Time Frequency Analysismentioning
confidence: 99%
“…Previous work has shown that hyperoxia induces changes in basic physiological parameters such as breathing and heart rate and in turn, these changes may directly or indirectly affect brain state or function Colrain et al, 1987;Desai et al, 2015;Pack et al, 1992;Tsanov et al 2014;Yackle et al, 2017). Indeed, hyperoxia is also known to induce changes in cerebral blood flow (Bergo and Tyssebotn 1995;Bew et al, 1994;Busija et al, 1980;Floyd et al, 2003; HYPEROXIA ON BRAIN ACTIVITY 4 Kety and Schmidt, 1948;Lund et al, 1999;Watson et al, 2000), which might also be expected to result in a functional change in the operation of the brain even given the fact that cerebral blood flow and brain state can show independence from each other, despite their typical tight correspondence (Bangash et al 2008;Braun et al 1997;Hajak et al 1994;Hofle et al 1997). In terms of pathological influences, there are also deleterious consequences of hyperoxia due to the production of reactive oxidative species (ROS), however, the exposure times necessary to observe these effects are quite long (~ 6 hours in normobaric conditions).…”
Section: Introductionmentioning
confidence: 99%
“…Raising alveolar Pcoz (PAco,) by breathing a C02-rich gas mixture dilates the cerebral vessels and increases blood flow, while lowering PACO~ by hyperventilation causes vasoconstriction and may endanger the oxygen supply [ l , 21. A reduced arterial oxygen content increases cerebral blood flow [3], but breathing 100% oxygen does not reduce cerebral perfusion [4].…”
Section: Introductionmentioning
confidence: 99%